Anterior knee pain after total knee arthroplasty: A multifactorial analysis - Laubach, Markus; Hellmann, Julian T. R.; Dirrichs, Timm; Gatz, Matthias; Quack, Valentin; Tingart, Markus; Betsch, Marcel (Journal of Orthopaedic Surgery, 2020)
Purpose: Dissatisfaction and an impaired quality of life after total knee arthroplasty (TKA) is often associated with postsurgical anterior knee pain (AKP). The underlying pathological mechanisms are not yet fully understood. Therefore, a multifactorial approach encompassing clinical and radiological parameters seemed reasonable and promising to investigate postsurgical AKP. Methods: In this cross-sectional study, 25 patients without and 25 patients with postsurgical AKP after unilateral TKA were randomly recruited from a larger cohort of patients. Multiple clinical and radiological parameters—including real-time shear wave elastography (SWE) to measure the patellar and quadriceps tendon elasticity—were acquired and subsequently associated with AKP. For statistical analysis, SPSS (IBM, version 25) was used. Results: In total 50 participants (58.0% men, mean age 63.42 years, mean body mass index 29.75 kg/m2), having different prosthetic designs implanted, were included. Independently of key covariates, the strength of the quadriceps muscle (p = 0.021), a thinner inlay (p = 0.041), and a lower position of the patella (p = 0.041) were associated with AKP. Although no correlation with AKP was found (p = 0.346, resp. p = 0.154), we observed significantly decreased Young’s modulus of the patellar and quadriceps tendons for the involved knee compared to the uninvolved knee (p < 0.001). Conclusion: In conclusion, quadriceps muscle strength, inlay thickness, and the patella position might be of particular relevance in avoiding postsurgical AKP. Future studies with larger sample sizes are needed to clarify the impact of quadriceps muscle strength and the postoperative patella position as well as the role of SWE as a personalized modifiable prediction marker.
CRIS-Team Scopus Importer:2022-07-20
Keywords: anterior knee pain; logistic regression analysis; multifactorial analysis; shear wave elastography; total knee arthroplasty